Single-cell RNA sequencing highlights the influence of innate and adaptive immune response mechanisms in psoriatic arthritis - Melanie R. Nielsen; Marie Skougaard; Marie Skougaard; Marie Skougaard; Clara Drachmann; Zara R. Stisen; Sisse B. Ditlev; Leon E. Jessen; Lars Erik Kristensen; Lars Erik Kristensen (Frontiers in Immunology)
IntroductionPsoriatic arthritis (PsA) is a chronic immune-mediated inflammatory disease displaying heterogeneous symptoms. However, the association between the clinical heterogeneity of PsA and disease immunopathogenesis remains poorly understood complicating diagnostic precision. A knowledge gap remains on whether it is possible to distinguish the clinical PsA phenotypes on the immune cellular level. The primary aim of the study was to explore the differences in gene expression profiles comparing PsA patients without cutaneous psoriasis (PsA-only) and PsA patients with cutaneous psoriasis (PsA/PsC). The secondary aim was to describe the transcriptional patterns in PsA patients compared with healthy controls.MethodsThe study applied single-cell RNA sequencing (scRNAseq) using the BD Rhapsody™ Single-Cell Analysis System to evaluate peripheral blood mononuclear cells (PBMCs) from 70 PsA patients and 10 healthy controls. Differential expression (DE) analysis and gene set enrichment analysis (GSEA) were applied to evaluate differentially expressed genes (DEGs) and enriched signaling pathways, respectively.ResultsThe DE analysis and GSEA comparing PsA-only and PsA/PsC patients with healthy controls, respectively, revealed divergent results involving both innate and adaptive immune mechanisms, which might be associated with differences in the clinical phenotype. No DEGs were discovered in the direct comparison of PsA-only and PsA/PsC patients.DiscussionThe single-cell transcriptome profiling provided insight into the heterogeneity of PsA patients as the discovered DEGs and the GSEA did demonstrate differences in signaling associated with inflammation comparing PsA patients with and without cutaneous psoriasis.